Confidence in COVID-19 vaccine effectiveness and safety and its effect on vaccine uptake in Tanzania: A community-based cross-sectional study. Issue 1 (31st December 2023) - Mtei, Monica; Mboya, Innocent B.; Mgongo, Melina; Manongi, Rachel; Amour, Caroline; Bilakwate, Julieth S.; Nyaki, Ahmed Y.; Ngocho, James; Jonas, Norman; Farah, Amina; Amour, Maryam; Kalolo, Albino; et al.
ABSTRACT: COVID-19 is a major public health threat associated with increased disease burden, mortality, and economic loss to countries and communities. Safe and efficacious COVID-19 vaccines are key in halting and reversing the pandemic. Low confidence in vaccines has been one of the factors leading to hesitancy. We aimed to assess the COVID-19 vaccine confidence (safety and effectiveness), associated factors, and its effects on vaccine uptake among general community members in Tanzania. This was a community-based cross-sectional survey conducted from December 2021 to April 2022 in six regions of Tanzania mainland and two regions in Zanzibar. Participants were interviewed using an electronic questionnaire. Multiple logistic regression models estimated odds ratios (ORs) and 95% confidence interval (CI) for factors associated with vaccine confidence. All analyses were performed using SPSS version 25.0. The study enrolled 3470 general Tanzanian community members; their mean age was 40.3 (standard deviation ±14.9) years, and 34% were males. The proportion of COVID-19 vaccine confidence was 54.6%. Geographical region, residence area, COVID-19 disease risk perception, and good knowledge of COVID-19 vaccines were significantly associated with COVID-19 vaccine confidence. Confidence in COVID-19 vaccines was associated with over three times higher odds of vaccine uptake. Confidence in COVID-19 vaccines was low in Tanzania. Innovative community engagement strategies and region-specific interventions are needed to improve comprehensive knowledge and address community perceptions and attitudes toward COVID-19 vaccines.